2003
DOI: 10.1210/jc.2002-021080
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation Activities on Skin Fibroblasts from a Short Child with Absence of One Copy of the Type 1 Insulin-Like Growth Factor Receptor (IGF1R) Gene and a Tall Child with Three Copies of the IGF1R Gene

Abstract: The type 1 IGF receptor (IGF1R) is required for normal embryonic and postnatal growth. The aim of this study was to determine whether we could detect abnormal IGF1R function in skin fibroblasts from children with an abnormal copy number of the IGF1R gene. We report two children with altered copy number of the IGF1R gene who presented with abnormal growth. Case 1 is a girl with intrauterine growth retardation, postnatal growth failure, and recurrent hypoglycemia. Pituitary function tests were normal. Routine ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
1
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 43 publications
10
89
1
7
Order By: Relevance
“…The phenotype variability in IGF-I insensitivity is most probably caused by differences in remaining IGF-I signaling or by a compensatory mechanism that up-regulates the expression of the normal IGF1R allele. In addition, a gene dose effect seems to play a role in postnatal growth as is demonstrated by the severe postnatal growth failure (K3.5 to K6.3 SDS) of patients with IGF1R haploinsufficiency due to a terminal 15q deletion, including the IGF1R gene (23, 25,26,[28][29][30]. The finding that trisomy of terminal 15q resulting in duplication of the IGF1R gene is associated with tall stature supports this hypothesis (58).…”
Section: Postnatal Growthmentioning
confidence: 76%
See 2 more Smart Citations
“…The phenotype variability in IGF-I insensitivity is most probably caused by differences in remaining IGF-I signaling or by a compensatory mechanism that up-regulates the expression of the normal IGF1R allele. In addition, a gene dose effect seems to play a role in postnatal growth as is demonstrated by the severe postnatal growth failure (K3.5 to K6.3 SDS) of patients with IGF1R haploinsufficiency due to a terminal 15q deletion, including the IGF1R gene (23, 25,26,[28][29][30]. The finding that trisomy of terminal 15q resulting in duplication of the IGF1R gene is associated with tall stature supports this hypothesis (58).…”
Section: Postnatal Growthmentioning
confidence: 76%
“…Stimulated GH secretion was normal in all tested patients (24,26,(28)(29)(30). Apparently, IGF1R haploinsufficiency has no major impact on GH and IGF-I secretion.…”
Section: Regulation Of Gh Secretionmentioning
confidence: 78%
See 1 more Smart Citation
“…The binding of IGF-I to its receptor induces receptor autophosphorylation in the intracellular kinase domain of the β-subunit and results in activation of the intrinsic tyrosine kinase activity of the IGF1R. Okubo et al 37 demonstrated increased rates of cell proliferation and autophosphorylation of IGF1R in skin fibroblasts from a patient with duplication of IGFR1 arising from a parental pericentric inversion. Gene dosage for IGF1R is increased in our patients and may result in increased binding of IGFs and overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hemizygosity for IGF1R causes primary IGF-I resistance despite normal GH and/or IGF-I levels in sera (12 -23). Nonetheless, limited information exists on the biological response to IGF-I in vitro in cultured cells and in vivo in patients with mono-allelic expression of the IGF-I receptor (18,23,24).…”
Section: Introductionmentioning
confidence: 99%